THE ANALYSIS OF METHODOLOGICAL APPROACH TEACHER TRAINING UNIVERSITY STUDENTS TO THE COMPETENT DECISION OF THE PROFESSIONAL PEDAGOGICAL TASKS - Ol’ga V. Buldasheva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The methodological approach teacher training university students to the competent decision of the professional pedagogical tasks are analyzed in this article. The author studies systemic, competence, integrative activity approach as the methodological basis preparation of students.